Peningkatan Literasi Kewirausahaan Berbasis Data bagi Mahasiswa Internasional - Indra Arifin Djashan; Denta Felli Ananda; Arton Bryan Prasetyo (Altifani Journal: International Journal of Community Engagement, 2026)
This community service activity aims to improve international students' understanding of data-driven entrepreneurship through a guest lecture program delivered by lecturers from STIE Trisakti, Jakarta, to college and high school students at Burapha University International College (BUUIC), Thailand. The session, themed "Entrepreneur and Data Analytics for Business," was designed to introduce the use of data analytics in business decision-making and entrepreneurial innovation. A total of 107 participants attended this activity and provided feedback through a post-activity survey. Descriptive analysis showed a very high level of Overall Satisfaction with an average score of 4.579 using a Likert scale of 1-5, reflecting a positive and relevant learning experience for participants. The integration of the BBQ Sales Prediction case study helped students understand how data is used to analyze sales patterns and formulate evidence-based business strategies. This activity not only enriched the insights of BUUIC students but also strengthened international academic collaboration between Indonesia and Thailand. Overall, this guest lecture program made a real contribution to improving data-driven entrepreneurship literacy and supporting the development of global competencies in participants.